The Right To A Healthful Environment In Nigeria: A Review Of Alternative Pathways To Environmental Justice In Nigeria - Abdulkadir, Abdulkadir Bolaji (Journal of Sustainable Development Law and Policy, 2025)
The Constitution of the Federal Republic of Nigeria includes in its Chapter Two on “Fundamental Objectives and Directives Principles of State Policy” provisions on the protection of the environment. However, these provisions are made unjusticiable by other provisions in the Constitution that oust the jurisdiction of the court to entertain any matter related to the enforceability of the provisions of chapter two of the Constitution, which includes the protection of environment. These ouster provisions have led to an explosion of scholarly views on the question of how best environmental rights could be constitutionally derived and protected in Nigeria. This paper aims to contribute to these debates. The paper explores how the right to a healthful environment can be derived and secured using other enforceable provisions in the Nigerian Constitution, and through other domesticated international instruments in Nigeria, to enhance access to environmental justice in Nigeria.